Quantitative Analysis of Bound Water Content in Marine Clay and Its Influencing Factors During the Freezing Process by Nuclear Magnetic Resonance - Xuehan Shan; Huie Chen; Chuqiao Meng; Zuojun Lv; Qingbo Yu; Zhaoxi Wang; Qing Wang (Journal of Marine Science and Engineering)
The change in bound water content with temperature is a core issue in studying temperature effects in clayey soils. This study used nuclear magnetic resonance (NMR) techniques to measure pore water in three types of marine clay, ranging from inland to coastal areas. The T2 cutoff values were proposed to distinguish between bulk water, capillary water, and bound water, and the curves of unfrozen water and bound water content with changing temperatures were obtained during the freezing process. Additionally, the impact of soil properties on bound water content was analyzed. The research findings indicated that the pore water in marine clay is dominated by bound water, and the change in bound water content with temperature in each soil layer can be divided into four stages: the trace phase change stage, the intense phase change stage, the transitional phase change stage, and the stabilizing stage. Further, the effect of soil properties such as organic matter content, soluble salt content, and cation exchange capacity on bound water content was illustrated, and clay content and bound water content were found not to be strictly positively correlated.